Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1302/0301-620x.85b5.14012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and natural history of deep-vein thrombosis after total hip arthroplasty

Abstract: here are many reports concerning the aetiology and prophylaxis of deep-vein thrombosis (DVT) but little is known about its natural history. The purpose of our study was to identify the incidence and site of DVT, the risk factors for pulmonary embolism and the natural history of DVT after total hip replacement (THR) in patients who do not receive any form of prophylactic or therapeutic treatment for DVT.Two hundred patients who had a primary THR were included: 100 had one-staged bilateral THR and 100 had unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 53 publications
2
18
0
4
Order By: Relevance
“…Further research is needed to determine the risk/benefit profile for the treatment of small and/or isolated subsegmental clots and determine if patients diagnosed with only small tertiary pulmonary emboli would benefit from not being treated. In our study, the overall incidence of detected PE was approximately 0.5%, which is an incidence consistent with that reported in the literature [2][3][4].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further research is needed to determine the risk/benefit profile for the treatment of small and/or isolated subsegmental clots and determine if patients diagnosed with only small tertiary pulmonary emboli would benefit from not being treated. In our study, the overall incidence of detected PE was approximately 0.5%, which is an incidence consistent with that reported in the literature [2][3][4].…”
Section: Discussionsupporting
confidence: 92%
“…Because of the low overall incidence of PE [1][2][3][4], it is unreasonable to perform postoperative CT scans on all orthopedic patients or even all patients who have undergone higher risk procedures like total joint arthroplasty. Such an approach would increase the risk of unnecessary radiation exposure to patients and would be imprudent from a cost-benefit analysis of health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, subjects of this study were all Japanese and the incidence of DVT may differ among various ethnic groups. Kim et al reported that Koreans undergoing THA have a low incidence of DVT [16,17], although others have reported that the incidence of DVT appears similar between Asian and Western populations [22]. We therefore cannot say whether the incidence in our population in fact differs from that of other populations.…”
Section: Discussionmentioning
confidence: 68%
“…[6][7][8] Ultra Sound Doppler has the sensitivity of 63%-94% to detect deep venous thrombosis as quoted in a meta-analysis. 9 There is a clear guideline on the preventive aspect of this complication as given by both AAOS and NICE.…”
Section: Discussionmentioning
confidence: 98%